Clinical and molecular characterization of adult patients with late-onset MTHFR deficiency - Marelli, Cecilia; Lavigne, Christian; Stepien, Karolina M; Janssen, Mirian C H; Feillet, Francois; Kožich, Viktor; Jesina, Pavel; Schule, Rebecca; Kessler, Christoph; Redonnet-Vernhet, Isabelle; Regnier, Adeline; Burda, Patricie; et al. (Journal of inherited metabolic disease, 2021)
5,10-Methylenetetrahydrofolate reductase (MTHFR) deficiency usually presents as a severe neonatal disease. This study aimed to characterize natural history, biological and molecular data, and response to treatment of patients with late-onset MTHFR deficiency. The patients were identified through the European Network and Registry for Homocystinuria and Methylation Defects and the Adult group of the French Society for Inherited Metabolic Diseases; data were retrospectively colleted. To identify juvenile to adult-onset forms of the disease, we included patients with a diagnosis established after the age of 10 years. We included 14 patients (median age at diagnosis: 32 years; range: 11-54). At onset (median age: 20 years; range 9-38), they presented with walking difficulties (n = 8), cognitive decline (n = 3) and/or seizures (n = 3), sometimes associated with mild mental retardation (n = 6). During the disease course, symptoms were almost exclusively neurological with cognitive dysfunction (93%), gait disorders (86%), epilepsy (71%), psychiatric symptoms (57%), polyneuropathy (43%), and visual deficit (43%). Mean diagnostic delay was 14 years. Vascular events were observed in 28% and obesity in 36% of the patients. One patient remained asymptomatic at the age of 55 years. Upon treatment, median total homocysteine decreased (from 183 μmol/L, range 69-266, to 90 μmol/L, range 20-142) and symptoms improved (n = 9) or stabilized (n = 4). Missense pathogenic variants in the C-terminal regulatory domain of the protein were over-represented compared to early-onset cases. Residual MTHFR enzymatic activity in skin fibroblasts (n = 4) was rather high (17%-58%). This series of patients with late-onset MTHFR deficiency underlines the still unmet need of a prompt diagnosis of this treatable disease.
Keywords: dospělí; Epilepsy; Female; věk při počátku nemoci; dítě; Seizures; Adult; mladý dospělý; ženské pohlaví; opožděná diagnóza; Adolescent; lidé; psychotické poruchy; Intellectual Disability; Muscle Spasticity; retrospektivní studie; epilepsie; Methylenetetrahydrofolate Reductase (NADPH2); Male; Delayed Diagnosis; Young Adult; Psychotic Disorders; lidé středního věku; Child; Age of Onset; Homocystinuria; mužské pohlaví; svalová spasticita; mentální retardace; Retrospective Studies; Middle Aged; mladiství; homocystinurie; záchvaty; methylentetrahydrofolátreduktasa (NADPH2); Humans